At the Very Edge of a Storm: The Impact of a Distant Cyclone on Atoll Islands - Tauisi Taupo; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2016)
The intensity of cyclones in the Pacific is predicted to increase and sea levels are predicted to rise, so an atoll nation like Tuvalu can serve as the `canary in the mine' pointing to the new risks that are emerging because of climatic change. Based on a household survey we conducted in Tuvalu, we quantify the impacts of Tropical Cyclone Pam (March 2015) on households, and the determinants of these impacts in terms of hazard, exposure, vulnerability and responsiveness. Households experienced significant damage due to the storm surge caused by the cyclone, even if the cyclone itself passed very far away (about a 1000km). This risk of distant cyclones has been overlooked in the literature, and ignoring it leads to significant under-estimation of the disaster risk facing low-lying atoll islands. Lastly, we constructed hypothetical policy scenarios, and calculated the estimated loss and damage they would have been associated with – a first step in building careful assessments of the feasibility of various disaster risk reduction policies.
Keywords: 330; cyclone; Tuvalu; impact